Syukur dan Pujian menurut Muhammad Shaleh Darat As-Samarani: Kajian atas QS. Al-Fatihah [1]:[2] Tafsir Faidh Ar-Rahman - Baihaki, Egi Sukma (Tanzil : Jurnal Studi Al-Quran, 2016)
Praise and gratitude (syukr) are closely related to forms of worshiping of a servant to his Lord. Many verses of the Qurâan show this as it is associated with favors that God has bestowed upon His creation. However, there are still many people who neglect and forget to thank and praise God for all the blessings that God has given to them. Either becauseÂ  ofÂ  theirÂ  ownÂ  humiliation,Â  asÂ  wellÂ  asÂ  theÂ  weaknessÂ  ofÂ  thoseÂ  whoÂ  areÂ  unable to understand the nature of gratitude and praise itself. This article will see how this message appears in (QS. al-FÄtiáºah [1]: 2) where Allah orders his worshipers to thank andÂ  praiseÂ  him,Â  whileÂ  GodÂ  HimselfÂ  WhoÂ  startedÂ  praisingÂ  Him.Â  Therefore,Â  theÂ  aim of this paper is to introduce how such views and ideas appear through Muhammad Sholeh Darat al-Samarani, mainly when interpreting (QS. al-FÄtiáºah [1]: 2) in his book, TafsÄ«r Faidh al-RaáºmÄn.